Phenomenology of non-verbal communication as a representation of sports activities - Liubov Karpets; Mykhailo Beilin (Слобожанський науково-спортивний вісник, 2018)
The priority of language professional activity in sports is such non-verbal communication as body language. Purpose: to delete the main aspects of non-verbal communication as a representation of sports activities. Material & Methods: in the study participated members of sports teams, individual athletes, in particular, for such sports: basketball, handball, volleyball, football, hockey, bodybuilding. Results: in the process of research it was revealed that in sports activities such nonverbal communication as gestures, facial expressions, physique, etc., are lapped, and, as a consequence, the position "everything is language" (Lyotard) is embodied. Conclusions: non-verbal communication is one of the most significant forms of communication in sports. Additional means of communication through the "language" of the body help the athletes to realize themselves and self-determination.